TOPONIMLERDIŃ KLASSIFIKACIYASÍ HAQQÍNDA - Seytniyazov, K.M. (SCIENCE and SOCIETY, 2024)
The world of geographical names is very diverse and interesting. Names consits the majority of language words. Different interpretations by scientists led to the classification of toponyms. Linguistic classification of toponyms is based on linguistic issues, and historical classification of geographical names is based on the age of toponymic layers.